Synthesis, Characterization, and Crystal Structure of Sodium (Methyl α-d-Mannopyranosid)uronate Monohydrate - Xu, Peng; Dauter, Zbigniew; Kováč, Pavol (Synthesis, 2014)
TEMPO (2,2,6,6-tetramethylpiperidine-1-oxyl)-mediated oxidation of methyl α-d-mannopyranoside with sodium hypochlorite gave sodium (methyl α-d-mannopyranosid)uronate, which was obtained as a crystalline monohydrate in ~70% yield without chromatography. Its purity was proved by NMR spectroscopy, a newly developed HPLC method, combustion analysis, and X-ray crystallography. The crystal structure, solved from synchrotron diffraction data in space group P212121, revealed that the packing of the uronate molecules is connected by an extensive network of hydrogen bonds, and that the Na+ ion is coordinated by six oxygen ligands from one water and three surrounding sugar molecules.
Keywords: mannuronic acid; oxidation; chemoselective methylation; TEMPO; HPLC